The ideologies of theory - Jameson, Fredric (London ; New York : Verso, 2008)
A collection of theoretical essays which were composed under a particular set of constraints - the need to explain the Marxist intellectual tradition within the bounds of literary criticism - thereby enlarging the conception of the literary text.
Metacommentary --
The ideology of the text --
Imaginary and symbolic in Lacan --
Criticism in history --
Symbolic inference; or, Kenneth Burke and ideological analysis --
Figural relativism; or, the poetics of historiography --
Modernism and its repressed; or, Robbe-Grillet as anti-colonialist --
Morality versus ethical substance; or, Aristotelian Marxism in Alasdair MacIntyre --
On Negt and Kluge --
Benjamin's readings --
Foreword to Jean-Francois Lyotard's The postmodern condition --
Foreward to Jacques Attali's Noise: the political economy of music --
The theoretical hesitation: Benjamin's sociological predecessor --
How not to historicize theory --
The vanishing mediator; or Max Weber as storyteller --
Architecture and the critique of ideology --
Pleasure: a political issue --
Of islands and trenches: neutralization and the production of Utopian discourse --
Beyond the cave: demystifying the ideology of modernism --
Reflections on the Brecht-Lukacs debate --
Marxism and historicism --
Periodizing the 60s --
Foreward to A.J. Greimas' On meaning: selected writings in semiotic theory --
On the sexual production of western subjectivity --
Space and congestion: Rem Kool Hass and S, M, L, XL --
Future city --
Marc Angenot and the literary history of a year --
On "cultural studies" --
The end of temporality.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Criticism; Ideology -- History -- 20th century; Philosophy, Modern -- 20th century; English literature